Challenges Faced by Married Muslim Women of Sri Lanka Studying in Higher Education Level - M.R.F. Afra; M.M.A. Abdullah; M.H.A. Munas (LECTURES: Journal of Islamic and Education Studies, 2023)
Islam is one of the religions which acknowledges and secure all of the fundamental rights of women including education. According to Islam, education is important and compulsory for both male and female. The aim of this study is to identify the challenges that face married Muslim women at their higher education. The research is descriptive in nature following qualitative approach to collect data with the semi-structured interview. However, support for the education of married women depends upon family attitude, educational status, financial stability and husband viewpoint. Furthermore, commitments of multiple roles and lower level of self-confidence of women are most significant challenges of their education. Especially in Sri Lanka, the traditional families think that higher education of women will affect the morals, confine freedom and make problem in their matrimonial life. It is suggested that researches and seminars are essential to be structured to change the perception of the Muslim society about women’s education in Sri Lanka. The result will be a fact finding to suggest to the policy makers in Sri Lanka on how to tackle the challenges facing married women in their higher education.